sofyan Pelaksanaan Pendidikan Karakter siswa di SMA Negeri 2 Halmahera Barat - Sofyan Umar (IAI DDI Polewali Mandar, 2020)
This research discuss about education character implementation of the student in SMA 2 Halmahera Barat. This aims to improve effectivity character construction through cultural school, spiritual activities and pramuka.The main problem is how the process of student character construction in SMA 2 Halmahera Barat running and is the system of student character construction through cultural school, spiritual activities and pramuka effective on using in the school. This research is a field research which aims to explaining the problems and get informations, datas in the research area. Analyzing the problems and the goals this research is using quantitative method more to descriptive. This research also doing collecting data through observation, structural interview and documentation. The result of the research shows that student character implementation in SMA 2 Halmahera Barat are through cultural school such as system order, practice of greeting, talking and smiling. The spiritual construction for the moslem through listening speech every monday morning, doing routine meeting in every week and month. For the Cristian, doing open usbu every monday morning and close usbu every friday, also doing teenager praying and household praying in the church or in the home. There is also character construction through pramuka which one of them is camping